2014
DOI: 10.1007/s10964-014-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Trajectories of Delinquency Throughout Adolescence

Abstract: Given that one of the most powerful predictors of adult crime is the presence of behavior problems in childhood and adolescence, there is a need to further understand factors that determine behavior patterns during this developmental stage. This study focuses on stressful life experiences such as exposure to delinquent peers, racial discrimination, as well as family characteristics such as parenting style and family transitions. Data come from four waves of the Family and Community Health Survey, an African-Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 59 publications
9
61
1
1
Order By: Relevance
“…Research – often in high-income countries – has clearly identified linkages between quality of parenting and positive child outcomes (e.g. (Cuevas et al, 2014)) but has also identified that there are potential differences across cultures in both parenting styles and their impacts on children (Bornstein, Putnick, & Lansford, 2011) in both the short and long term (S. Z. Evans, Simons, & Simons, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research – often in high-income countries – has clearly identified linkages between quality of parenting and positive child outcomes (e.g. (Cuevas et al, 2014)) but has also identified that there are potential differences across cultures in both parenting styles and their impacts on children (Bornstein, Putnick, & Lansford, 2011) in both the short and long term (S. Z. Evans, Simons, & Simons, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The expectation was that the intervention participants would have a more positive view of their future and their associations. Both the intervention and the no intervention groups acknowledged the influence of friends on their criminal behavior and gang involvement (Evans et al, 2016;Lenzi et al, 2015). However, the intervention group brought about discussion of cutting ties with old friends in favor of making new, positive friends who could be used as peer role models (Hoge et al, 1996).…”
Section: Social Influences and Cohesion Through Rugbymentioning
confidence: 99%
“…Having a non-deviant good friend or being a member of a peer group who disapproves of antisocial behavior has a direct protective effect against youth violence and delinquency (Evans, Simons & Simons, 2014;Herrenkohl, Tajima, Whitney & Huang, 2005).…”
Section: Social Factorsmentioning
confidence: 99%
“…In addition to parental support, peer groups form a critical context for healthy growth and development. Peer relationships influence various youth behaviors such as aggression, delinquency, depression and substance use (Asscher et al, 2014;Evans, Simons & Simons, 2014;Assink et al, 2015). A study conducted by Reynolds & Crea (2015) explored the multiple factors that account for peer influence related to adolescent delinquency and depression.…”
Section: Benefits Of Social Support On Mental Illnessmentioning
confidence: 99%